1988
DOI: 10.1111/j.1467-8306.1988.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Interdecadal and Interannual Climatic Variations and Their Effect on Pennsylvania Climate

Abstract: The variability of Pennsylvania winter climate is shown to b e t h e result of mechanisms working on two distinctly different time scales: interdecadal and interannual. lnterdecadal variability is associated with hemispheric changes in large-scale atmospheric circulation regimes. During periods of zonal flow, Pennsylvania temperatures are above normal, while meridional flow is associated with below-normal temperatures. Precipitation is near normal during zonal regimes, but can b e either very dry (as it was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 43 publications
5
93
0
Order By: Relevance
“…For instance, the rain-on-snow flood of March 1936(Lichtenwalner 1936 and the Hurricane Agnes flood of June 1972(Bailey et al 1975 are evident in the unsmoothed data. Similarly, the decadelong drought of the 1960s (Cook & Jacoby 1983) and the very wet decade of the 1970s (Yarnal & Leathers 1988) appear in the smoothed curve. Despite the record snowfalls of the 1990s and the record wet year of 1996, from this perspective the 1990s were not outstandingly wet in the SRB.…”
Section: Streamflowmentioning
confidence: 99%
“…For instance, the rain-on-snow flood of March 1936(Lichtenwalner 1936 and the Hurricane Agnes flood of June 1972(Bailey et al 1975 are evident in the unsmoothed data. Similarly, the decadelong drought of the 1960s (Cook & Jacoby 1983) and the very wet decade of the 1970s (Yarnal & Leathers 1988) appear in the smoothed curve. Despite the record snowfalls of the 1990s and the record wet year of 1996, from this perspective the 1990s were not outstandingly wet in the SRB.…”
Section: Streamflowmentioning
confidence: 99%
“…Several atmospheric GCMs have been shown to underestimate the amplitude of the PNA pattern associated with the 1997-1998 El Niño event (Kang et al, 2002), although Renshaw et al (1998) showed that HadAM3, the atmospheric component of HadCM3, correctly reproduces the changes in the frequency distribution of the PNA index associated with the phases of ENSO. As with the NAO, most studies of the PNA have focused on interannual and longer timescales, although the PNA varies on all timescales from days to decades (Blackmon et al, 1984;Yarnal and Leathers, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between the 2 approaches is in the way the atmospheric classification and the surface environment relate to one another (Yarnal 1993).…”
Section: Synoptic-climatological Theory and Methodsmentioning
confidence: 99%
“…If he or she first complles a classification of weather types over the region and then relates the classes to days with high precipitation acidities, the investigator is employing a circulation-to-environment scheme. Yarnal (1993) identified 5 categories of circulation-to-environment schemes: manual synoptic typing (e.g. Lamb 1972); correlation-based map-pattern classification (Lund 1963 In contrast, with the environment-to-circulation approdch the investigator identifies the atmospheric circulation associated with particular environmental conditions at the surface.…”
Section: Synoptic-climatological Theory and Methodsmentioning
confidence: 99%